Epidemiology and genotypic distribution of noroviruses in patients with acute gastroenteritis in developing and developed countries - Kumthip, Kattareeya; Khamrin, Pattara; Maneekarn, Niwat (Annals of Research Hospitals, 2019)
Norovirus (NoV) is one of the major causes of viral sporadic and outbreak-associated gastroenteritis across all age groups both in developing and developed countries (1). With the implementation of rotavirus vaccines, the rotavirus-associated gastroenteritis cases have continuing declined and NoV infection has become the leading cause of acute gastroenteritis in children younger than 5 years of age (2-4). The NoV-associated mortality has been estimated in children aged less than 5 years in developing countries up to 218,000 deaths per year (5,6). In addition, NoV-associated deaths in adults in upper middle- and high-income countries have also been estimated at 2,000 to 13,000 deaths per year (7). Currently, no NoV vaccine is available, even though several NoV vaccine candidates are in the process of development (8).